Theory of Critical Legal Studies and the General Election and Presidential Election 2019 (Case Study: Critical Legal Studies of IAIN Ponorogo Students) - Dewi Iriani; Martha Eri Safira; Arief Budiono (Universitas PGRI Madiun, 2021)
In 2019, presidential and legislative candidates were elected simultaneously on April 17, 2019. Likewise, students are given the right to choose the mind and critical spirit of problem formulations 1) What are the obstacles in implementing the 2019 simultaneous election according to Fakultas Syariah student Iain Ponorogo? 2) What are the factors of Fakultas Syariah student Iain Ponorogo so that they are interested in choosing the Presidential and Vice-Presidential candidate pair No. 1 and the candidate pair for President and Vice President No. 2? 3) What are the factors that make Falkutas Syariah student Iain Ponorogo in choosing a legislative candidate? This research is a qualitative research with the type of field research. Research results 1) The implementation of the 2019 general election students do not understand because the KPU does not provide socialization, unknown candidates, election violations, many KPPS officers have died which has been shown, the factor of the figure of the presidential and vice-presidential candidates is also their consideration in giving their voting rights, choosing candidates because they follow their parents. 3) The student factor chooses a candidate from if they know the candidate choosing from the vision and mission of the candidate, but if the candidate is not known to choose from a political party, he chooses because he gets basic food and money